2019
DOI: 10.1016/j.bone.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar bone mineral asymmetry in elite cricket fast bowlers

Abstract: Bone responds to mechanical loading by increasing bone mineral density (BMD) and/or bone area to enhance bone strength at the site of the greatest strain. Such localised adaptation has not been demonstrated at the spine. The aim of this study is to determine if BMD and/or bone mineral content (BMC) differs between dominant (ipsilateral to bowling/throwing arm) and non-dominant sides of the vertebrae in cricket fast bowlers, and whether this asymmetry differs according to stress fracture or disc injury history.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…It could be suggested that a more holistic approach to the identification of those at risk of stress fracture injury is required, rather than relying on BMD measurements alone. This is exemplified in the current study, as the average T scores of athletes with and without stress fractures were higher than that considered to be a risk for adverse bone health, and no differences were present between the two groups Previous studies in athletes assessing BMD and stress fracture injury have based their findings on a relatively low number of stress fracture cases (n = 2 [11]; n = 6 [6]; n = 20 [8]; n = 27 [13]), which be a reason for the variable results shown. As the present study contained 50 athletes with a history of stress fracture, the results provide more definitive data on the association between BMD and stress fracture and injury.…”
Section: Bone Characteristicsmentioning
confidence: 52%
See 1 more Smart Citation
“…It could be suggested that a more holistic approach to the identification of those at risk of stress fracture injury is required, rather than relying on BMD measurements alone. This is exemplified in the current study, as the average T scores of athletes with and without stress fractures were higher than that considered to be a risk for adverse bone health, and no differences were present between the two groups Previous studies in athletes assessing BMD and stress fracture injury have based their findings on a relatively low number of stress fracture cases (n = 2 [11]; n = 6 [6]; n = 20 [8]; n = 27 [13]), which be a reason for the variable results shown. As the present study contained 50 athletes with a history of stress fracture, the results provide more definitive data on the association between BMD and stress fracture and injury.…”
Section: Bone Characteristicsmentioning
confidence: 52%
“…Currently, whole body dual-energy x-ray absorptiometry (DXA) measurements are used as a method to assess an individual's risk of stress fracture injury [5]. lower bone mineral density (BMD), bone mineral content (BMC) and reduced bone structural properties have been associated with stress fracture risk in some athletic population (cricketers (lumbar spine BMD, [6]), runners (tibial strength, [7]; hip BMD, [8]), triathletes (tibial cortex; [9]) and female athletes (trabecular BMD; [10]), but not in others (endurance athletes (triathletes and runners-whole body, lumbar spine and hip) [11] and runners (whole body, lumbar spine, hip, radius) [12][13]. The contrasting findings may be accounted for by the sport participated in, the likely difference in the pathophysiology of injury caused by the differing activity status of the participants (amateur and elite populations) in the aforementioned studies and the difference in the anatomical scan site.…”
Section: Introductionmentioning
confidence: 99%
“…Site specific (pelvis, upper and lower limbs) changes in BMC have also been shown between pre-season and end-of-season and between midseason and end-of-season in elite football players, but individual responses to specific training modalities were not recorded [23]. Another issue is that many of these studies have only utilized DXA for the measurement of bone characteristics [11,14,21], meaning that no measures of volumetric bone characteristics, which are vital in accurately determining bone strength [24], have been made. A prospective longitudinal study design, with multiple measurement points over the course of a season, and the attainment of both volumetric and areal bone density measurements is required to provide accurate data on bone structural characteristics.…”
Section: Modelling Changes In Bone and Body Composition Over A Season...mentioning
confidence: 99%
“…Fast bowlers deliver the ball at velocities often in excess of 40 m·s −1 (16) in an attempt to reduce the reaction time in which batters can interpret the path of the ball and have annual match workloads in excess of 2000 balls (19). Previous research using two-dimensional–based dual x-ray absorptiometry (DXA) has demonstrated that elite male fast bowlers have high lumbar (L1–L4) BMD (BMD, 1.56 ± 0.16 g·cm −2 ; Z score, 2.45 ± 1.24), particularly on the contralateral side of the lumbar spine (opposite to the bowling arm), which increases inferiorly, peaking at L4, where BMD is 14.6% greater than on the ipsilateral side (20). This asymmetric presentation of the lumbar spine is likely in response to the asymmetric fast bowling technique, which may put greater strain within the contralateral side of the lumbar spine, in relation to the bowling arm.…”
mentioning
confidence: 99%
“…Recent research has implicated the motion of the lumbopelvic joint in the etiology of LBSI in cricket fast bowlers (27). Although localized low BMD could contribute to LBSI risk in fast bowlers (20), there is little understanding of the effect of fast bowling technique on the bone adaptation in the contralateral side of the lumbar spine in cricket fast bowlers.…”
mentioning
confidence: 99%